Genetic Variants Related to Increased CKD Progression—A Systematic Review - Filipe S. Mira; Bárbara Oliveiros; Isabel Marques Carreira; Rui Alves; Ilda Patrícia Ribeiro (Biology)
The incidence and prevalence of chronic kidney disease (CKD) are increasing worldwide. CKD is associated with high morbidity, premature mortality, and high healthcare costs. Genetic variants may influence CKD development and progression. This study aimed to identify the associations between allelic variants and CKD progression. We performed a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed, Embase, and Cochrane Central databases were used for data collection. Hereditary causes of CKD were excluded from the analysis. A total of 38 reports were included. The selected studies included cohort studies, case-control studies, and genome-wide association studies (GWASs). The studies involved patients of different ethnicities and with comorbid diseases. Several genetic variants were identified in genes that encode proteins related to metabolic processes, oxidative stress, immune regulation, the renin–angiotensin–aldosterone pathway, and epigenetics, among others. These genetic alterations can affect protein function and lead to renal damage, impacting CKD development and progression. Gene polymorphisms can influence CKD progression. Many of these are population-specific, and their relevance may be influenced by the presence of other diseases and environmental factors. Larger studies are needed to confirm the associations described here.